2018
DOI: 10.3390/ijfs6010032
|View full text |Cite
|
Sign up to set email alerts
|

Testing Efficiency of the London Metal Exchange: New Evidence

Abstract: This paper explores the market efficiency of the six base metals traded on the LME (London Metal Exchange) using daily data from January 2000 to June 2016. The hypothesis that futures prices 3M (3-month) are unbiased predictors of spot prices (cash) in the LME is rejected based on the false premise that the financialization of commodities has been growing. For the robustness check, monthly data is analyzed using ordinary least squares (OLS) and GARCH (1,1) models. We reject the null hypothesis for all metals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…One of the probable reasons for this is liquidity, which means higher liquidity provides a better investment environment for money managers. Notice that the trading volumes of aluminum, copper, and zinc are relatively higher compared to other base metals in LME (see details in Park and Lim (2018)). This finding is strong and in line with the first hypothesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the probable reasons for this is liquidity, which means higher liquidity provides a better investment environment for money managers. Notice that the trading volumes of aluminum, copper, and zinc are relatively higher compared to other base metals in LME (see details in Park and Lim (2018)). This finding is strong and in line with the first hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…They employed COT 3 The LME is the world's largest futures exchange in the metal industry, including base metals and spot (cash), futures (3M), and various option contracts. Park and Lim (2018) provided a good discussion of the LME. They found that the LME was an inefficient market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using bivariate FIGARCH model, they showed that spot and three-month aluminum and copper volatilities followed long memory process, but no evidence that the volatilities processes were fractionally cointegrated. Park & Lim (2018) examined whether the price volatility of the LME changed within a sample period (January 2000-June 2016) to check the possibility of time varying volatility. They reported that the LME's volatility was somewhat larger post-crisis compared to pre-crisis for all base metals except nickel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The LME address daily rolling three-month (3M) futures contracts that are different from those in other commodity markets, which are based on monthly prompt dates. (Park & Lim, 2018) The LME is traded electronically but also traded through the open outcry. These characteristics are somewhat different from other asset markets, which can possibly impact the LME's volatility process (Figuerola-Ferretti & Gilbert, 2008).…”
mentioning
confidence: 99%